2016
DOI: 10.1126/science.aac9185
|View full text |Cite
|
Sign up to set email alerts
|

Pure H conduction in oxyhydrides

Abstract: A variety of proton (H(+))-conducting oxides are known, including those used in electrochemical devices such as fuel cells. In contrast, pure H(-) conduction, not mixed with electron conduction, has not been demonstrated for oxide-based materials. Considering that hydride ions have an ionic size appropriate for fast transport and also a strong reducing ability suitable for high-energy storage and conversion devices, we prepared a series of K2NiF4-type oxyhydrides, La(2-x-y)Sr(x + y)LiH(1-x + y)O(3-y), in the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
229
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 188 publications
(253 citation statements)
references
References 37 publications
19
229
0
1
Order By: Relevance
“…Recently, the conduction of H ¹ in solids has been verified for a BaH 2 and La 2¹x¹y Sr x+y LiH 1¹x+y O 3¹y oxyhydride system (LSLHO), and the results showed that H ¹ is a new charge carrier for the transport of hydrogen in solids. 4,5 Particularly, realization of a battery reaction using LSLHO as a solid electrolyte in our previous work have confirmed not only the capability of the LSLHO to act as an H ¹ solid electrolyte but also the possibility of developing electrochemical devices based on H ¹ conduction. 5 Hydride ions are attractive as charge carriers because they have an ionic radius similar to those of oxide and fluoride ions in crystal lattices, which are suitable for rapid ionic conduction and also exhibit strong reducing properties with a standard redox potential of H ¹ /H 2 (¹2.3 V) comparable to that of Mg/Mg 2+ (¹2.4 V).…”
Section: Introductionmentioning
confidence: 89%
See 4 more Smart Citations
“…Recently, the conduction of H ¹ in solids has been verified for a BaH 2 and La 2¹x¹y Sr x+y LiH 1¹x+y O 3¹y oxyhydride system (LSLHO), and the results showed that H ¹ is a new charge carrier for the transport of hydrogen in solids. 4,5 Particularly, realization of a battery reaction using LSLHO as a solid electrolyte in our previous work have confirmed not only the capability of the LSLHO to act as an H ¹ solid electrolyte but also the possibility of developing electrochemical devices based on H ¹ conduction. 5 Hydride ions are attractive as charge carriers because they have an ionic radius similar to those of oxide and fluoride ions in crystal lattices, which are suitable for rapid ionic conduction and also exhibit strong reducing properties with a standard redox potential of H ¹ /H 2 (¹2.3 V) comparable to that of Mg/Mg 2+ (¹2.4 V).…”
Section: Introductionmentioning
confidence: 89%
“…The Rietveld analysis was carried out on the basis of previously reported structural models of LaSrLiH 2 O 2 synthesized at high pressure. 5 A total of four sites were assigned to La/Sr, Li, H, and O, respectively, for the refinement of the tetragonal phase: 4e ð0; 0; zÞ site for La and Sr, 2a ð0; 0; 0Þ site for Li, 4c ð0: 1=2; 0Þ site for H, and 4e ð0; 0; zÞ site for O in I4/mmm (space group 139). Figures 4-5 show the synchrotron X-ray and neutron Rietveld refinement patterns, and Tables 1-2 summarizes the refinement structural parameters for the sample.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations